2009
DOI: 10.1038/jid.2008.320
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Synthesis Is Suppressed in Dermal Fibroblasts by the Human Antimicrobial Peptide LL-37

Abstract: LL-37 is a human cathelicidin antimicrobial peptide that is released in the skin after injury and acts to defend against infection and modulate the local cellular immune response. We observed in human dermal keloids that fibrosis was inversely related to the expression of cathelicidin and sought to determine how LL-37 influenced expression of types I and III collagen genes in dermal fibroblasts. At nano-molar concentrations, LL-37 inhibited baseline and transforming growth factor-β-induced collagen expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…In addition, some inflammatory markers, such as IL-10, are modulators for healing and repair of the infarcted myocardium, and promoting more effective tissue repair may reduce deleterious remodeling, which is the leading cause of heart failure and death after AMI 27) . As LL-37 is involved in tissue healing and repair [18][19][20] , plasma LL-37 levels may be useful for predicting future cardiac events related to remodeling. Furthermore, the combination of blood HNP1-3 and LL-37 measurement, or together with other blood parameters, such as CRP, is possibly a multi-biomarker strategy for prognosis in patients with myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some inflammatory markers, such as IL-10, are modulators for healing and repair of the infarcted myocardium, and promoting more effective tissue repair may reduce deleterious remodeling, which is the leading cause of heart failure and death after AMI 27) . As LL-37 is involved in tissue healing and repair [18][19][20] , plasma LL-37 levels may be useful for predicting future cardiac events related to remodeling. Furthermore, the combination of blood HNP1-3 and LL-37 measurement, or together with other blood parameters, such as CRP, is possibly a multi-biomarker strategy for prognosis in patients with myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the divergence between local and systemic LL-37 levels detected in STEMI is probably due to flow cessation by sudden total coronary artery occlusion, which tem- has beneficial effects. Park et al 18) reported that LL-37 protein expression was lower in keloid tissue than in normal skin and LL-37 inhibited collagen production in human dermal fibroblasts, suggesting that LL-37 may have antifibrotic action during the wound repair process. LL-37 may also induce fibroblast proliferation, which contributes to tissue repair 19) .…”
Section: Ll-37 and Acute Myocardial Infarctionmentioning
confidence: 99%
“…Skin TMA sections (Cybrdi, Shanxi ChaoYing, Xi'an, China), which included 80 samples (12 squamous cell carcinoma, 12 basal cell carcinoma, 12 malignant melanoma, 10 condyloma acuminatum, 6 basal cell papilloma, 1 cyst, 1 verruca vulgaris, 6 hyperplasia, 5 chronic inflammation, 5 cancer-adjacent tissue, 5 cancer-adjacent normal dermatic tissue, and 5 normal dermatic tissue) were assayed as previously described (Park et al, 2008) (Table 2). Briefly, the anti-LL-37 primary antibody (Santa Cruz Biotechnology, Santa Cruz, CA) was applied followed by the Polink-2 plus ® polymer HRP detection system (Zhongshan Jinqiao, Beijing, China).…”
Section: Tma and Immunohistochemistrymentioning
confidence: 99%
“…The activity of the ERK1/2 pathway is regulated by many different stimuli, including growth factors, cytokines, viral infection, transforming agents and carcinogens, which can then influence collagen synthesis. [26][27][28] In conclusion, female SUI is associated with reduced levels of p-ERK1/2 compared with controls, and inhibition of the ERK1/2 signalling pathway inhibits collagen types I and III synthesis in vaginal wall fibroblasts. It is possible that abnormalities in ERK1/2 activation may be involved in the pathogenesis of female SUI.…”
Section: Discussionmentioning
confidence: 99%